2009
DOI: 10.1103/physrevb.79.155311
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing nitrogen solubility in GaAs and InAs by surface kinetics: Anab initiostudy

Abstract: Nitrogen solubility at GaAs and InAs ͑001͒ surfaces has been studied employing density-functional theory calculations. The effect of the surface reconstruction and the reconstruction-induced surface strain on N solubility was analyzed in detail, considering the various surface layers and sites. The stability phase diagrams for the considered systems were constructed, and based on them an estimate of the N concentration has been deduced for the thermodynamically accessible and relevant range of chemical potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Indeed, as demonstrated in Ref. 14 under these extreme N rich growth conditions N concentrations up to few percents can be easily achieved consistent with experimental observations 80, 81.…”
Section: Dilute Nitride Semiconductorssupporting
confidence: 88%
See 3 more Smart Citations
“…Indeed, as demonstrated in Ref. 14 under these extreme N rich growth conditions N concentrations up to few percents can be easily achieved consistent with experimental observations 80, 81.…”
Section: Dilute Nitride Semiconductorssupporting
confidence: 88%
“…In addition, the determination of the kinetic barriers is essential to identify the incorporation mechanism that is operational and dominant for a given growth environment (fluxes, temperature). By employing a comprehensive set of ab initio calculations and combining them with surface thermodynamics 14 and adatom incorporation kinetics 84, we were able to accomplish a complete understanding of the factors that control the incorporation of N in dilute nitride alloys 14, 13. To discuss the ideas and possibilities offered by this approach we give in the following a brief review on the solubility phase diagrams of N at GaAs(001) surface and show how they can be applied to study the various incorporation mechanisms.…”
Section: Dilute Nitride Semiconductorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang and Wei [18] suggested that potential energy of N species can increase the solubility of N in the host lattice up to 8 orders of magnitude. Abu-Farsakh and Nargebauer [19] further suggested that substitutional N atom solubility can be enhanced by surface kinetics. Their calculation showed that the incorporation of adatom in the second anion layer needs the lowest formation energy and is responsible for the high N atom solubility.…”
Section: Resultsmentioning
confidence: 97%